Optimalisasi laboratorium komputer sebagai center of statistical development di Fakultas Ekonomi dan Bisnis Islam IAIN Salatiga - Rofiuddin, Mohammad (Nur Science Institute, 2021)
The not yet optimal computer laboratory as a center of statistical development can affect the competencies possessed by students or lecturers in education, research, and community service. So, it is necessary to optimize the computer laboratory as a center of statistical development following the needs of the academic community and industry. Efforts include computer laboratory governance, installing the latest statistical/econometric software in computer laboratories, socialization of computer laboratory usage rules, simulation of data exploration using STATA, Eviews, Shazam software. As a result, these activities have been carried out well, although the authors still find some obstacles, and students can attend training and learn statistical or econometric software needed to support the teaching and learning process.